Nonlinear dynamic analysis using microplane model for concrete and bond slip model for prediction of behavior of nonseismically detailed RCC beam-column joints - Sharma, Akanshu; Genesio, G.; Reddy, G. R.; Eligehausen, R. (Journal of Structural Engineering, 2025)
Under a seismic event, beam-column joints of a reinforced concrete structure need special attention due to their highly complex behavior under seismic loads, which is marked by a combination of huge shear forces, diagonal tension and high bond stresses in the reinforcement bars, all brittle modes of failure. The non-seismically detailed joints generally fare poorly under the event of an earthquake, undergoing joint shear failure or bond failure or both. Analytical modeling of bond slip failure between reinforcement and concrete is very important in order to obtain the correct failure modes, strength and ductility values. In this paper, a comparative study by means of nonlinear dynamic analysis, without and with bond modeling, for one exterior and one interior joint tested under quasi-cyclic loads is presented. The analyses presented in the paper were performed with the FE Code MASA, developed at the Universität Stuttgart and capable of 3D nonlinear dynamic analysis of quasi-brittle materials, like concrete, based on a microplane material model with relaxed kinematic constraint. The discrete bond model for reinforcement used, essentially consists of onedimensional nonlinear springs with a bond-slip relationship proposed by Eligehausen and later developed by Lettow. The results verify the efficiency of the modeling technique and clearly show that in order to make realistic predictions on strength, ductility and failure modes for the joints, the bond slip needs to be modeled.